The Influence of Delayed Payment Obligation on Purchase Decision of Household: Evidence from Nigerian Data - Ojonta, Obed I. (Universitas Islam Indonesia, 2022)
The purpose of this study is to examine how delayed payment obligation influences household purchase decision in Nigeria. Unlike the large of existing studies, this study used binary regression model estimation and draws a dataset of 2019 General Household Survey with sample size of 2911 household for the analysis. The stylized facts from the dataset revealed more share of rural household than their counterparts in urban household. Interestingly, the results show that delayed payment obligation is positive and significantly influence purchase decision of household in Nigeria. But when the household is disaggregated into rural and urban household, the result shows that some household that barrowed from friends and family and household that reduced food consumption expenditure have positive and significant influence on purchase decision in both rural and urban household while household that received assistance from friends and family has positive and significant influence on purchase decision by rural household. This study recommends delayed payment obligation for important factor to drive purchase decision by household. This could be achieved through policy formulation that will promote delayed payment obligation.